PENGEMBANGAN VIDEO PEMBELAJARAN PADA MATERI PESAWAT SEDERHANA UNTUK MEMBANTU SISWA DENGAN KETERBATASAN PENDENGARAN (TUNARUNGU) - Muing, Hasnia; Saehana, Sahrul (Universitas Tadulako, 2022)
The purpose of this study is to know the worthiness of learning video by using sign language developed and to know the student's response to it on simple machine materials to help deaf students. The research used Research and Development (R & D) with the Brog and Gall model. The learning video developed on simple machine materials is worthy of helping deaf students with material aspects in good category media aspects, and very good sign languange aspects. The response of deaf students to the learning video developed on simple machine materials is in very good categories.